Thinking Clearly about Psychology V1 : Matters of Public Interest - Cicchetti, Dante (Book collections on Project MUSE., 1987)
Provide a brief historical account of how the various societal, clinical, and academic conceptions about child maltreatment have evolved / review national studies on the incidence of child maltreatment, illustrating how epidemiological estimates vary as a function of the definitions of child maltreatment that are employed / delineate reasons why we believe that a nosology of child maltreatment is necessary to advance our knowledge of the causes, consequences, and treatment of child abuse and neglect / outline a system of operational criteria we have developed for the child maltreatment from Ch.